Dietary sodium intake in urban and rural Malawi, and directions for future interventions. Issue 3 (30th June 2018) - Prynn, Josephine E; Banda, Louis; Amberbir, Alemayehu; Price, Alison J; Kayuni, Ndoliwe; Jaffar, Shabbar; Crampin, Amelia C; Smeeth, Liam; Nyirenda, Moffat
ABSTRACT: Background: High dietary sodium intake is a major risk factor for hypertension. Data on population sodium intake are scanty in sub-Saharan Africa, despite a high hypertension prevalence in most countries. Objective: We aimed to determine daily sodium intake in urban and rural communities in Malawi. Design: In an observational cross-sectional survey, data were collected on estimated household-level per capita sodium intake, based on how long participants reported that a defined quantity of plain salt lasts in a household. In a subset of 2078 participants, 24-h urinary sodium was estimated from a morning spot urine sample. Results: Of 29, 074 participants, 52.8% of rural and 50.1% of urban individuals lived in households with an estimated per capita plain salt consumption >5 g/d. Of participants with urinary sodium data, 90.8% of rural and 95.9% of urban participants had estimated 24-h urinary sodium >2 g/d; there was no correlation between household per capita salt intake and estimated 24-h urinary sodium excretion. Younger adults were more likely to have high urinary sodium and to eat food prepared outside the home than were those over the age of 60 y. Households with a member with previously diagnosed hypertension had reduced odds (OR: 0.59; 95% CI: 0.51, 0.68) of per capita household plain salt intake >5 g/d, compared with those where hypertension was undiagnosed. Conclusions: Sodium consumption exceeds the recommended amounts for most of the population in rural and urban Malawi. Population-level interventions for sodium intake reduction with a wide focus are needed, targeting both sources outside the home as well as home cooking. This trial was registered at clinicaltrials.gov as NCT03422185.